Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. The degree to which the supervisory model contributes to enabling the schools of the Oasis Education Office in Jeddah to practice procedural research from the point of view of school employees Ms. Afra Ahmad Shuwaylan, Ms. Hana Mohammed Hussein Abualella, Ms. Aisha Ali Rayih Al-Asmari, Ms. Rasha Ezzat Hussein Ahmed, Ms. Hend Hdyban Al-Jehani 2. Women’s Attitude Towards Engaging in Sports Activities in The Sultanate of Oman Together towards engaging in sports activities (from Feb to Sep 2023) Ms. Alya Masaud Hamdoon Alsiyabi 3. Challenges of financing higher education in the Kingdom of Saudi Arabia - Taibah University is a model Ms. Enas Moedh Alharbi 4. Irrational thoughts as a predictor of depression and burnout in health practitioners Ms. Al-Reem Abdullah Al-Owayied, Dr. Saleh Mohammed Al-Rajhi 5. The effectiveness of a program based on the Assessment, Evaluation and Programming System (AEPS) in developing social communication skills for children with autism spectrum disorder Mr. Laith Emad Al-Ronkose, Prof. Eman Khleif Al-Zboon 6. The Emotional Balance and Its Relationship with Social Support among the Elderly in Care Homes in the Governorates of Bethlehem and Jericho Ms. Ala Said Abu Haltam, Co-Prof. Fadwa Abdallah Al-Halabiyah 7. School Life Quality from the Perspective of Secondary School Students in Arab Schools in Palestine 1948 Ms. Ghadeer Mostafa Abu Khdair, Ms. Areen Khaled Jabarien, Ms. Noran Sohail Igbaria